The influence of transformational leadership and the physical work environment on innovative work behavior mediated by knowledge sharing in the MKGR organization of Banten province - Bayu Astapati Rahayu; Amir Arifudin; Henri Khairuddin; John Chaidir; Haerofiatna Haerofiatna (Enrichment : Journal of Management, 2026)
This research explores how transformational leadership and the physical work environment shape knowledge-sharing practices and innovative work behavior, both through direct relationships and through indirect pathways. A quantitative approach was employed, with data gathered through questionnaires administered to members of the MKGR Mass Organization in Banten Province. Using proportional random sampling, responses were obtained from 65 participants. The collected data were processed and analyzed using multiple linear regression with the support of SPSS version 30. The findings indicate that transformational leadership significantly influences innovative work behavior, as does the physical work environment. Knowledge sharing also plays a crucial role in fostering innovative behavior. In addition, both transformational leadership and the physical work environment significantly affect knowledge-sharing activities. Importantly, knowledge sharing functions as a mediating variable, strengthening the influence of transformational leadership and the physical work environment on innovative work behavior